The Effect of Leverage, Liquidity and Total Asset Turnover on Financial Performance (A Case Study of Property & Real Estate Sector Companies for the 2020–2024 Period) - Putri Shofi Adilla; Nurul Kamila (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The property and real estate sector plays a strategic role in supporting economic growth and attracting investment in Indonesia. However, fluctuations in corporate financial performance indicate the importance of identifying the financial factors that influence profitability. This study aims to analyze the effect of leverage, liquidity, and total asset turnover on the financial performance of property and real estate companies listed on the Indonesia Stock Exchange during the 2020–2024 period. A quantitative research approach was employed using secondary data obtained from the annual financial statements of listed companies. The sample consisted of 24 companies selected through purposive sampling, resulting in 120 observations. Financial performance was measured using Return on Assets (ROA), while leverage, liquidity, and activity were represented by the Debt-to-Equity Ratio (DER), Current Ratio (CR), and Total Asset Turnover (TATO), respectively. Data were analyzed using multiple linear regression, supported by classical assumption tests, coefficient of determination, partial (t-test), and simultaneous (F-test) analyses with IBM SPSS Statistics version 27. The findings reveal that DER and CR do not have a significant effect on ROA, indicating that debt utilization and liquidity management alone are insufficient to improve profitability. In contrast, TATO has a positive and significant effect on ROA, demonstrating that efficient asset utilization contributes to better financial performance. Simultaneously, DER, CR, and TATO significantly influence ROA, suggesting that these financial indicators collectively contribute to the financial performance of property and real estate companies.